The Time Course of Event-Related Brain Potentials in Athletes’ Mental Rotation With Different Spatial Transformations - Feng, Tian; Li, Yawei (Frontiers in Behavioral Neuroscience, 2021)
Studies have found that athletes outperformed non-athletes in mental rotation tasks with both object-based and egocentric transformations, but the effect of sport expertise on the processing stages (i.e., perceptual stage, rotation stage, and decision stage) remains conflicted. Bearing the view that the stages occur sequentially and the high temporal resolution of event-related brain potentials, this study focused on brain processing during mental rotation and was designed to determine the time course of electrophysiological changes in athletes and non-athletes. A total of 42 divers and non-athletes were recruited for the study. A mental body rotation task with object-based and egocentric transformation conditions was conducted, and the reaction time, accuracy, performance stages, N2 latency, amplitude, and the amplitude of rotation-related negativity were recorded. Behavioral results demonstrated higher accuracy for athletes at 120° and 180°. Moreover, as compared to non-athletes, the enlarged amplitude of N2 and rotation-related negativity were confirmed in both transformations for athletes and were correlated with the performance stages and athletes’ professional training years. The present study provided a deeper insight into the relationship between sports training, behavior performance, and brain activity.